Peran kepala bidang pembinaan sekolah dasar dalam mewujudkan pendidikan berkualitas di dinas pendidikan kota palangka raya - Mesyi Mesyi; Nurul Hikmah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the role of the Palangkaraya City Education Office in developing elementary schools towards quality education. The background of this study is based on the importance of basic education as a foundation in forming competencies/academics, life skills, and character of students, as well as the challenges in the form of quality disparities between schools in the city center and suburban areas. The research method used is qualitative. Data collection techniques used are interviews, observations, and documentation studies. The subjects in this study were the Head of the Education Office, Head of the Elementary School Development Division, school supervisors, principals, and teachers. The data validation techniques used were source triangulation and technical triangulation.Data were analyzed through the stages of data condensation, data presentation, and conclusion drawing. The results of the study indicate that the Education Office has played a strategic role through teacher distribution, improving the competence of teaching staff, providing infrastructure, and implementing academic and managerial supervision. However, this study found obstacles in the form of budget limitations, uneven teacher distribution, limited supervisors, and unequal access to training. The conclusion of this study confirms that the Palangkaraya City Education Office plays a crucial role in improving the quality of basic education, but innovative strategies and more inclusive policies are needed to optimally achieve educational equality.